Method to determine van der Waals potential energy of particle interactions for soil clay by dynamic light scattering. (21st March 2021) - Li, Qinyi; Shi, Weiyu; Yang, Qingyan
Abstract: Soil particle interaction forces/energies control aggregation and breakup/dispersion processes, which further profoundly affect a series of soil micro‐ and macro‐processes. For soils with complex compositions, it is the interaction energy of different particles that determines particle aggregation and aggregate breakdown/dispersion. However, measuring the interaction energy for complex systems remains a challenge. In this study we proposed a method to measure this van der Waals potential energy using the dynamic light scattering technique. Firstly, the mathematic relationship between the mean aggregation rate and van der Waals potential energy was established. The mean aggregation rates of particles for either simple or complex systems can be facilely determined by the dynamic light scattering technique. Secondly, for verifying the availability of the suggested method, montmorillonite suspensions in four different electrolyte solutions (NaCl, KCl, MgCl2 and CaCl2 ) were respectively employed to measure the van der Waals potential energy, which equals −17, 817 ± 857 J mol −1 or −7.22 ± 0.304 kT with an average deviation of 4.22%; this directly verified the reliability of the suggested method. Thirdly, the proposed method was also verified indirectly and independently by the ratio of the electrostatic potential energy of particles to the presence of K + and Na +, as compared with the ratios from the determined van der Waals potential energy of this study and from cation adsorption selectivity. Considering the dynamic light scattering technique has been widely applied for characterizing soil/clay/humus/microbe aggregation, the proposed method should be appropriate for measuring the van der Waals potential energy for all those systems. Highlights: Develop a simple method to measure the mean interaction energy for complex systems. The mathematic relationship between the mean aggregation rate and van der Waals energy was established. A method to measure the van der Waals potential energy using the dynamic light scattering technique has been proposed. The van der Waals potential energy in the soil system can be measured in different electrolyte solutions and KCl might be the best one.